Tempo e aceleração social na perspectiva da teoria e da clínica psicanalíticas - Martins, Osvaldo Costa (2019)
This thesis discusses the question of time and temporality in psychoanalytic theory and clinical practice perspective, establishing interlocution with the sociological debates on the current hegemonic temporal regime, namely, social acceleration. The problematic of time was made accessible by the psychoanalytical perspective since it allowed questioning the subject and its unconscious determinations, from clinical listening. This has shown that the speaking being is crossed by several temporalities and that the regime of social acceleration tends to reduce them to a single one, producing negative effects on time to understand. In this context, it inquired the notions of time proposed by Sigmund Freud and Jacques Lacan. Thus, clinical vignettes are given to discuss the notions of time in psychoanalysis and the unique arrangements that, in the neuroses, are produced to equate the questions that time imposes to the speaking being. It is a research in psychoanalysis with the psychoanalytical method. The concept of social acceleration established by Hartmut Rosa and the notions of Chronos, Kairos, and Aion guided the debates in this thesis. Four moments delimitated the course of this work throughout the chapters: 1. The resumption of Ancient Greece culture elements to evidence other conceptions of time and compare them with the cut brought by modernity; 2. Distinction of the cuts effects operated by modern thought on the social organization of time; 3. Discussion of Freud and Lacan theories on time and questioning the idea of timelessness of the unconscious; 4. Resource to the theory of Jacques Lacan speeches to think the social acceleration and its relations with the speaking being and the temporalities. Finally, it concluded it is not acceleration and time famine that produce anguish, but that anguished people adhere to the ideals and injunctions of acceleration as a resource to face loneliness, helplessness (Hilflosigkeit) and the precariousness of brands symbolic that contemporary culture offers to deal with it.